Evaluation of tensile adhesion strength in mortar for coating with incorporation of crushing sand - Erba, Leandro Augusto; Azambuja, Maximiliano dos Anjos (Revista Nacional de Gerenciamento de Cidades, 2022)
The use of crushed sand, a by-product generated in quarries during the process of manufacturing crushed stone used in civil construction, can reduce the consumption of natural sand, reducing the environmental impact of the extraction of this material. In this sense, this research aims to evaluate the influence of replacing natural sand with crushed sand on the tensile bond strength of mortars. Mortars were made with crushed sand from quarries in the region of Bauru/SP, performing 3 percentages of substitution, in mass, of natural sand by crushed sand: 10%, 20% and 30%, plus a reference with 100% sand natural, totaling 4 strokes. All mortars were made in accordance with ABNT NBR 13276/2005. The performance of the mortars was evaluated through the tensile bond strength test, as recommended by the ABNT NBR 13528/2019 standard. In the end, it can be said that it is feasible to use crushed sand to replace natural sand in the percentage of up to 20% for making mortars for coating external walls, which showed the best adhesion results. It was also found that, for internal coating, it is possible to use up to 30% of crushed sand, without compromising the performance of the mortar.